PENGARUH VARIASI KONSENTRASI HEMISELULOSA DALAM PEMBUATAN MIKROPARTIKEL - Dalimunthe, Gabena Indrayani; Lubis, Minda Sari; Sitinjak, Iyustri Ririn (UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
Hemicellulose (corncob isolated) is a natural polymer that is nontoxic, mucoadhesive, biodegradable, biocompatible and has a low level of immunogenicity, so it is very good to be used as a drug carrier and in the development of pharmaceutical preparations. Hemicellulose in this study will be made in the size of microparticles, where the microparticles are preparations with a particle size of 1-1000 m. The microparticles in this study were encapsulated by varying the concentration of hemicellulose as a carrier combined with STPP (Sodium tripolyphosphate) as a cross-linker or as a crosslinking agent and Propylene Glycol (PG) as a solvent and metronidazole as a model drug. Variations in the concentration of hemicellulose made were 100 mg, 200 mg, 300 mg, 400 mg and 500 mg. The purpose of this study was to see how the effect of variations in hemicellulose concentration on particle size and the characterization of the formed microparticles. The microparticle characterization results obtained have particle sizes at F1= 453.36 m, F2= 635.93 m, F3= 717.32 m, F4= 893.22 m and F5= 918.57 m. The yield obtained at F1 = 80.29% , F2 = 82.50%, F3 = 90.47%, F4 = 87.65% and F5 = 90.75% while the solubility test results show that the microparticles are easily soluble in an atmosphere. alkaline and at high temperatures, while at low temperatures and acid conditions it is difficult to dissolve until practically insoluble.